EVALUATION PERFORMANCE OF BREAD WHEAT PURE LINES TO GROWTH TRAITS AND PROLINE - & Baktash, Dhahi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field experiments were carried out at Abu- Graib Research Station- Agricultural Research Office- Ministry of Agriculture during 2014- 2015 season to investigate the performance of 225 pure lines of bread wheat (Triticum aestivum L.), which at sixth generation after crossing among local and exotic genotypes (during 2008 to 2014) with their parents. The experiment was conducted using Simple Lattice Design with three replications. The results were revealed highly significant differences among genotypes for all studied traits. The genotypes 39 and 192 had higher number of days to 50% flowering (140 days), the longest period of physiological maturity 159 days of genotype 49. The highest means of flag leaf area (80.4 cm2)  were found by genotype 199, the genotype 101 gave higher flag leaf angle (720), the genotype 28 gave higher plant height (94.6 cm), higher number of tillers (47.4 tillers) produced by genotype 99, genotype 207 gave higher length of spike (19.3 cm). The genotype 156 superior in number of spikelet spike-1 and highest proline content (6.91 µ moles mg-1)  in flag leaf was found in  genotype 39.